THE EFFECTS OF DEPRIVING CHILDREN FROM THEIR PARENTS ON THEIR SOCIAL COMMUNICATION WITH THEIR PEERS, FROM THE POINT OF VIEW OF TEACHERS IN JORDAN - Najihah Abd Wahid; Ola Yahea Aljamal; Anas Mohd Yunus; Hafsa Yahea Aljamal, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study aims at revealing the effects of depriving the child from interacting with his or her peers by the parents, as seen from the perspectives of teachers in the primary stage in Irbid governorate, in Jordan. In order to achieve the objectives of the study, a study tool has been developed to measure parental deprivation on the nature of communication for their children, in addition to distributing a questionnaire to collect a sampled study that includes (190) male and female teachers, who are randomly selected. The study concludes that there is a significant and positive relationship between depriving the children from their parents, as compared to their relationship with their peers.